2020
DOI: 10.1007/s42452-020-03545-w
|View full text |Cite
|
Sign up to set email alerts
|

Specific chemical incorporation of l-DOPA and functionalized l-DOPA-hyaluronic acid in Candida antarctica lipase: creating potential mussel-inspired bioadhesives

Abstract: Mussel adhesives proteins have been extensively studied as a promising alternative in bioadhesives due to their ability to provide durable anchoring under different surfaces in seawater. These charasteristics have been attributed to the presence of the reduced catechol form, 3,4-dihydroxyphenylalanine (DOPA) of its structure. However, its practical applications have been limited due to drawbacks with natural extraction. Here, a novel method have been described for site-specific chemical incorporation of l-3,4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Based on biomechanical studies, it is known that these bio-adhesive polymers have better strength of bio-adhesion when compared to fibrin glue, but they also have a poorer strength of bio-adhesion than cyanoacrylates on bovine cortical bone specimens. Excellent biocompatibility was also demonstrated in in vitro cell testing, so this bio-based adhesive can be a promising candidate for clinical utilization [21,42,[46][47][48].…”
Section: Sources and Types Of Bio-based Adhesivesmentioning
confidence: 82%
“…Based on biomechanical studies, it is known that these bio-adhesive polymers have better strength of bio-adhesion when compared to fibrin glue, but they also have a poorer strength of bio-adhesion than cyanoacrylates on bovine cortical bone specimens. Excellent biocompatibility was also demonstrated in in vitro cell testing, so this bio-based adhesive can be a promising candidate for clinical utilization [21,42,[46][47][48].…”
Section: Sources and Types Of Bio-based Adhesivesmentioning
confidence: 82%
“…35 These polymers have been recently used for stabilization of multimeric enzymes, 19 and also, we observed important influences on the selectivity and specificity of enzymes after their modification. 18,36,37 Dextrans with molecular weights of 6 kDa and 2000 kDa, respectively, were modified firstly using sodium periodate to create dextranaldehyde (Dext-Asp). The chemical incorporation of aspartic acid molecules into dextran-aldehyde polymer resulted in the final dextran-aspartic acid polymers called Dext6kDa and Dext2000kDa.…”
Section: Synthesis and Characterization Of Ag Nanoparticles-enzyme Hy...mentioning
confidence: 99%
“…14 Recent studies have demonstrated that the physical or chemical modification of enzymes generates novel bioconjugates with improved catalytic properties. [18][19][20][21] This is a very important issue, in particular, when a cascade process is developed. These novel nanobiohybrids could have a pivotal advantage over other systems since they are able to exhibit an enzymatic and metallic activity in the same compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme lid oligopeptide (orange). egy recently reported 31 by us using N-acetyl-tyrosine (Ac-Tyr) as molecule (Fig. S6 †).…”
Section: Preparation and Characterization Of The New Pd-gtl Enzymesmentioning
confidence: 99%
“…of NHS (37.46 mg) were added in 5 mL of H 2 O adjusted to pH 4.8-5.2. 31 This solution was allowed to react for 1 h. Then, 0.5 mL (50 eq.) of the previous solution was added to 3.5 mL of H 2 O adjusted to pH = 7 and 0.5 g of GTL or GTL-C114 immobilized on butyl-Sepharose protein at r.t., and the mixture was left to react overnight.…”
Section: Preparation Of the Pd-enzyme Conjugatesmentioning
confidence: 99%